The Interplay between Child and Maternal Health: Reciprocal Relationships and Cumulative Disadvantage during Childhood and Adolescence. (March 2014) - Garbarski, Dana
While many studies use parental socioeconomic status and health to predict children's health, this study examines the interplay over time between child and maternal health across childhood and adolescence. Using data from women in the National Longitudinal Study of Youth 1979 cohort and their children ( N = 2, 225), autoregressive cross-lagged models demonstrate a reciprocal relationship between child activity limitations and maternal health limitations in direct effects of child activity limitations on maternal health limitations two years later and vice versa—net of a range of health-relevant time-varying and time-invariant covariates. Furthermore, there are indirect effects of child activity limitations on subsequent maternal health limitations and indirect effects of maternal health limitations on subsequent child activity limitations via intervening health statuses. This study examines how the interplay between child and maternal health unfolds over time and describes how these interdependent statuses jointly experience health disadvantages.